Perbedaan Peningkatan Hasil Belajar Biologi Siswa antara Model Problem Based Learning dengan Model Inquiry Learning - Yunita Wardianti; Linna Fitriani; Wayan Ema Astuti (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2019)
This study aims to determine the improvement of student biology learning outcomes using the Problem Based Learning (PBL) model and Inquiry Learning model in Class X of Lubuklinggau 2 Public High School. This research is a quantitative descriptive research using quasi-experimental methods. The population in this study were all students of Class X Lubuklinggau 2 State Senior High School, amounting to 391 students, while the research samples were class X.7 amounting to 39 students as experimental class I and class X.10 totaling 40 students as experimental class II obtained using techniques cluster sampling. The research data was obtained by the test technique in the form of essay questions. Data analysis techniques with t test. The results of the study, based on the results of the analysis with the t test on the final value, can be concluded that Ho is rejected and Ha is accepted because of the value of Sig. (2-tailed) of 0.513 greater than α = 0.05. Conclusion, the increase in biology learning outcomes of students with Problem Based Learning learning models is higher than the increase in student biology learning outcomes with the Inquiry Learning model Keywords: problem based learning, inquiry learning, improving learning outcomes